Effect of oxygen tension on in vitro viability and development of dog follicles enclosed within the ovarian cortex - Pereira, Leda Maria Costa [UNESP]; Lopes, Maria Denise [UNESP]; Songsasen, Nucharin (Wiley, 2019)
Oxygen concentration has been shown to influence in vitro viability and growth of ovarian follicles. The present study examined the effect of oxygen tension on in vitro development of dog follicles enclosed within the ovarian cortex. Ovaries were obtained from domestic dogs (age, 8 months to 2 years), and cortical fragments were recovered. The cortices were then incubated on 1.5% (w/v) agarose gel blocks within a 4-well culture plate containing Eagle Minimum Essential Medium (MEM). Ovarian follicles within the tissues were processed for histology and assessed for follicle density, viability and diameter immediately after collection (Control) or after 2 or 5 days of in vitro incubation. Apoptotic cells were assessed using TUNEL assay. Comparisons of follicular viability and diameter were performed using analysis of variance followed by Tukey's test (p < 0.05). Comparisons of follicle density and apoptosis among treatments were conducted using Non-parametric Kruskal–Wallis test followed by Friedman's test (p < 0.05). No difference (p > 0.05) in follicle density was observed among groups at Day 2 of in vitro culture. However, the density of follicles within cortices cultured in 20% oxygen for 5 days significantly reduced compared to the Control and those incubated in 5% concentration. The viability of cultured follicles in all treatments decreased (p < 0.05) compared to the Control after 2 days incubation, and this value further reduced (p < 0.05) in 20% oxygen group at Day 5. There were no differences in the percentages of apoptotic follicles between the two treatment groups (p > 0.05). Nevertheless, after 5 days of culture, the percentage of TUNEL-positive follicles increased significantly (p < 0.05) in cortices incubated in 20% oxygen environment. In conclusion, our findings demonstrated that 5% oxygen level was superior to 20% concentration in sustaining in vitro viability of dog follicles enclosed within the ovarian cortex.
Keywords: dogs; ovarian follicle; oxygen tension